Effectiveness of narrative health message on attitude towards gaming disorder among adolescents at selected school of Patna - Sahu, Priyanshi; Nair, Rathish; Krishnaveni Murugesan, R.; K., Sathiyakala; Monica, Merlin (International Journal Of Community Medicine And Public Health, 2023)
Background: Games are generally seen to be beneficial activities but recently it gave rise concern towards people who play digital/video games for prolong hours as it interferes with personal, professional and academics, which is defined as symptoms of internet gaming disorder, that has been recently added in ICD-11 and DSM-5 for further study. Knowledge regarding IGD will help to prevent further prevalence of IGD and manage its harmful physical and mental issue. This study aimed to assess the prevalence of Internet gaming disorder among adolescent students at selected school of Patna, to evaluate the effectiveness of narrative health message on attitude towards gaming disorder among adolescents at selected school of Patna and to determine the association between demographical variables and pre-test attitude score. Methods: A quantitative research approach and pre-experiment (one group pre-test post-test) research design was used. About 76 participants were selected for the study using convenient sampling technique from class 8, 9 and 10 from selected school of Patna. Data was analysed by using descriptive and inferential statistics. Results: In pre-test 88.2% participants had positive attitude and 11.8% had negative attitude regarding internet gaming disorder. After implementation of narrative health message there were 92.1% participants had positive attitude and 7.9% had negative attitude The mean post-test attitude score of 76.91±11.717 was higher than the mean pre-test attitude score of 71.62±9.874. The calculated ‘t’ valve 4.421 was significant at p value 0.001. Conclusions: The study concludes that narrative health message regarding internet gaming disorder was effective.